METHODS OF IMPROVING PROFESSIONAL GRAPHIC COMPETENCE OF FUTURE INFORMATION TECHNOLOGY TEACHERS - Arzikulov Husan Normurod ugli (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
In this article, teachers provide students with the necessary technologies to learn and put them into practice. This is important in improving teachers' professional graphic competence, helping them to better prepare and teach students in the field of graphic design. These methods are important for teachers to get good results in improving their professional graphic competence, and their students are instructed to learn the necessary technologies and apply them in practice.